Characteristics and Frequency of Chipping Effects in Near‐Contact Gunshot Wounds. Issue 3 (13th December 2016) - Amadasi, Alberto; Mazzarelli, Debora; Merli, Daniele; Brandone, Alberto; Cattaneo, Cristina
Abstract: The presence of "chipping" or "flaking" around the edges of gunshot entry wounds has been described among the characteristics of gunshot wounds in bone. In this study, the real frequency of such a peculiar feature was investigated. The presence of "chipping" was assessed on 22 gunshot wounds fired at a near‐contact range on bovine ribs with 9‐mm bullets. As controls, five samples were shot with a 3 cm range, and five from 40 cm. In 77% of cases shot at near‐contact range, a detachment of small fragments of the upper layers of bone was detected, mainly with a circumferential disposition, whereas this feature was lacking in control samples. The study demonstrated the frequency of "chipping" and that it may probably be due to a combined ballistic effect of impact of the bullet itself and expansion of gases. It may be thus considered indicative of close‐range shots.